Perylenequinone derivatives from the endolichenic fungus Phialocephala fortinii. Issue 9 (3rd May 2023) - Song, Jintong; Xie, Fei; Luan, Xiaoyi; Xu, Ke; Qian, Lilin; Lu, Jinghui; Chang, Wenqiang; Wang, Xiaoning; Lou, Hongxiang
Abstract: Five undescribed perylenequinone derivatives (PQDs) phialocephalarins H − L (1  − 5 ), together with two known PQDs phialocephalarins A − B (6, 7 ) and one known spirobisnaphthalene palmarumycin P3 (8 ) were isolated from the endolichenic fungus Phialocephala fortinii. Their structures were elucidated on the basis of NMR and HRESIMS data as well as electronic circular dichroism (ECD) calculations. Compounds 1, 2, 4, and 6  − 8 were evaluated for cytotoxic activities against NCI-H460, NCI-H446, PC3, and EC109 cell lines. The results showed that compounds 1, 2, 6, and 8 showed cytotoxic activities against EC109 cells with IC50 values ranging from 24.5 to 33.3  μ M. Graphical Abstract: UF0001